Experimental analysis of combustion characteristics on a variable compression ratio engine fuelled with biodiesel (castor oil) and diesel blends - Singh B.; Shukla S.K. (My University, 2025)
Castor biodiesel was used to investigate the combustion characteristics of a variable compression ratio engine with blending ratio of B00 to B50 and compression ratio from 15 to 18. After extensive experimental work and observation, the effect on various parameter like mean gas temperature, cylinder pressure variation, net heat release, and mass fraction burned are compared with compression ratio and blending ratio. Observations have been drawn on the effects of the above parameters with various inputs. Mean gas temperature increases with compression ratio for all blending ratios and gives maximum value for B00. Cylinder pressure increases with compression ratio and maximum value is obtained at compression ratio 18 for B50. Net heat release decreases with compression ratio and maximum value is obtained for B00 at compression ratio 15. Mass fraction burned is better for B20 and poor for B50 for compression ratio 15 and 18. © 2016 Informa UK Limited, trading as Taylor & Francis Group.